HINODE study: haemophilia A in infancy and newborns – protocol for a prospective, multicentre, observational study evaluating the coagulation potential and safety of emicizumab prophylaxis - Shouichi Ohga; Hirosuke Inoue; Keiji Nogami; Masahiro Takeyama; Masataka Ishimura; Daisuke Nosaka; Keisuke Iwasaki; Chika Mitsui (BMJ Open)
Introduction Emicizumab prophylaxis is approved for people of all ages with haemophilia A (HA) including infants and children. Although previous studies have demonstrated the efficacy and tolerability of emicizumab in infants with HA, real-world data on emicizumab use in infants are limited. The Haemophilia A in Infancy and NewbOrns: multi-instituional prospective observational study to assess the efficacy anD safety of Emicizumab (HINODE) study aims to evaluate the coagulation potential and safety of emicizumab prophylaxis in infants with congenital HA from birth to <12 months of age.Methods and analysis This is a multicentre, observational study conducted in Japan in infants with congenital HA aged <12 months who are receiving or are scheduled to receive prophylactic emicizumab at an approved dosing regimen: 1.5 mg/kg weekly, 3 mg/kg every 2 weeks or 6 mg/kg every 4 weeks. The target inclusion is 50 infants. The primary endpoint is to evaluate the relationship between global coagulation test parameters (using clot waveform analysis and thrombin generation assay) and plasma emicizumab concentrations in infants aged from 6 to <12 months. Secondary endpoints include evaluating coagulation profiles in infants aged <6 months and changes between the age of <6 and 6 to <12 months. Additionally, coagulation parameters will be evaluated with the in vitro addition of anti-idiotype antibodies against emicizumab or the addition of a factor VIII product in infants aged from 6 to <12 months. The study will also evaluate adverse events and bleeds.Ethics and dissemination The study was approved by the MINS Clinical Trial Review Committee (no. 230214) and will be conducted in compliance with the Declaration of Helsinki, the Act on the Protection of Personal Information and the Guidance of Ethical Guidelines for Medical and Biological Research Involving Human Subjects. Written informed consent for participation in the study will be obtained from a legally acceptable representative. Results will be published in scientific/medical journals and presented at international congresses.Trial registration number Japan Registry of Clinical Trials; jRCT1031230264.